Inhibitors in mild/moderate haemophilia A: An update - Franchini, Massimo; Salvagno, Gian Luca; Lippi, Giuseppe (Thrombosis and Haemostasis, 2006)
The development of inhibitors in patients with mild/moderate hemophilia A is an increasingly recognized occurrence and is manifested by the patients’ bleeding pattern becoming more severe. Inherited (hemophilia genetic mutations) and acquired (type and delivery of factor VIII replacement therapy) factors have been associated with an increased likelihood of developing factor VIII inhibitors. Although the use of bypassing agents (i.e. activated prothrombin complex concentrates and recombinant factor VII activated) has been demonstrated to be effective in controlling bleeding episodes in patients who develop factor VIII inhibitors, the limited data available in the literature are insufficient to determine the optimal approach to the eradication of inhibitors (i.e. immune tolerance induction, immunosuppression or both) for this group. Particular attention should be directed to the prevention of this complication in those patients with mild/moderate hemophilia recognized to be at increased risk of developing a factor VIII inhibitor. In conclusion, large prospective trials are warranted in order to elucidate the many still unclear pathogenic and therapeutic aspects of the development of inhibitors in patients with mild/moderate hemophilia A.
Keywords: Inhibitors; bleeding; mild hemophilia A